Psychiatry of disasters. Organization of the work of a psychiatrist outpatient consultative reception - Shapovalova LA; Shapovalov KА (Annals of Psychiatry and Treatment - Peertechz Publications, 2019)
Introduction: The predicted increase in anthropogenic, technogenic, social, military, possible space disasters and emergencies attracts the attention of health organizers, doctors of specialists and especially psychologists and psychiatrists in connection with the need to provide assistance to the victims, as well as to develop principles, strategies and tactics, methods and means of providing timely psycho-psychiatric care. The aim of the work: Was to justify the need for the psychiatrist to prepare an outpatient consultative reception for work in emergency situations of catastrophes, natural disasters and terrorist acts.